A synoptic review of Caryophyllaeus Gmelin, 1790 (Cestoda: Caryophyllidea), parasites of cyprinid fishes - Barcak, Daniel; Oros, Mikulas; Hanzelova, Vladimira; Scholz, Tomas (Folia parasitologica, 2017)
Tapeworms of the genus Caryophyllaeus Gmelin, 1790 (Caryophyllidea: Caryophyllaeidae), common parasites of cyprinid fishes, are reviewed and taxonomic status of 42 nominal taxa that have been placed in the genus during its long history is clarified. The following seven species occurring in the Palaearctic Region are recognised as valid: C. laticeps (Pallas, 1781), C. auriculatus (Kulakovskaya, 1961), C. balticus (Szidat, 1941) comb. n. (syn. Khawia baltica Szidat, 1941), C. brachycollis Janiszewska, 1953, C. fimbriceps Annenkova-Chlopina, 1919, C. syrdarjensis Skrjabin, 1913, and newly described Caryophyllaeus chondrostomi sp. n. (= C. laticeps morphotype 4 of Bazsalovicsová et al., 2014) from common nase, Chondrostoma nasus (Linnaeus), found in Austria and Slovakia. The new species differs by the paramuscular or cortical position of preovarian vitelline follicles, a large, robust body (up to 64 mm long), conspicuously long vas deferens, flabellate scolex with small wrinkles on the anterior margin, and anteriormost testes located in a relatively short distance from the anterior extremity. Caryophyllaeus kashmirenses Mehra, 1930 and Caryophyllaeus prussicus (Szidat, 1937) comb. n. are considered to be species inquirendae, C. truncatus von Siebold in Baird, 1853 and C. tuba von Siebold in Baird, 1853 are nomina nuda. Data on the morphology, host spectra, distribution and known life-cycles of valid species are provided. Phylogenetic interrelations of four species of the genus including its type species and newly described C. chondrostomi were assessed based on an analysis of sequences of lsrDNA and cox1. A key to identification of all valid species of Caryophyllaeus is also provided.
Keywords: tapeworms; systematics; mužské pohlaví; cestodózy; phylogenetic relationships; Cyprinidae; Slovakia; Slovenská republika; ženské pohlaví; freshwater fish; zvířata; Palaearctic Region; nemoci ryb; fylogeneze; Cestoda; Fish Diseases; Cestode Infections; Female; Phylogeny; identification key; Male; Animals